Features of autonomous inertial positioning on hypersonic vehicles - Мельник, Виктория Николаевна; Карачун, Владимир Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The work concerns the nature of powerful shock action of hypersonic flying vehicles on mechanical systems of autonomous inertial positioning to define the deviation of the main axes of directional gyroscope by the derived N-wave while operating the vehicle. In addition to that, attention is stressed on the necessity to take into account the inertial sensors of Eulerian’s inertial forces Qα and Qβ in analytic calculated model, as a result of elastically intense state of impedance surface of gyroscope suspension in conditions of growing polyharmonical fuselage roll. In the frameworks of precession theory, in the assumption of smallness of Eulerian angles, for the case of asynchronous and synchronous roll there are values of drift α(t) and β(t) of the main axis of directional gyroscope relative to the axes of suspension, which outline additional errors of positioning of autonomous sensors and guidance devices in conditions of hypersonic motion. Received results serve as scientific base for the further improvement of the accuracy of positioning systems, in the first place pilotless planes (drones). Created calculated model of powerful shock action at the speed up to 20 M will enable to understand better the nature of this phenomenon and improve performance characteristics of hypersonic vehicles during its operation.